SPIRITUALITY AND RESILIENCE IN PATIENTS SUFFERING FROM CANCER - Soratto, Maria Tereza (2016)
Resilience is the ability to vanquish adversities, strength, resistance, overcoming in the wake of disease. Current research, featuring a descriptive and quality approach, identifies the importance of spirituality in resilience in patients with cancer and hospitalized in hospital cancer unit. Current analysis was developed with ten patients treated in a cancer clinic of a big, high complexity hospital in the southern region of the state of Santa Catarina, Brazil. Data analysis was undertaken with the Content Analysis Technique. Patients underscored the difficulties they had to cope with due to sickness and reported the transformations in family routine, daily life and their belief in God. People with cancer think that there is a spiritual influence on resilience to face the process of sickness and treatment. The nursing team should understand and valorize the relationship between spirituality and coping with cancer. Spiritual care in nursing must be considered the basis of humanization, the guiding principle in care ethics.